MAKNA DALAM GELAR: UPAYA MEMUDAHKAN MEMAHAMI MEGALITIK NIAS - Ketut Wiradnyana (Naditira Widya, 2009)
It is necessary to know physical and non-physical aspect of the megalithic remains at Nias to comprehend its significance. Recognizing Nias’ physical aspects does not directly grasp the essence of its megalithic culture and describe the people who once built the remnants. Therefore, it is necessary to understand its non physical aspect, such as names and titles of nobility of Nias community, because it is important part of their culture and act as symbol of characteristic, kinship, social standing and culture territory. This article discusses the importance of understanding the names and titles or nobility to futher explain the significance of megalithic remains in Nias.